Pengaruh Customer Relationship Management dan Islamic Corporate Governance Terhadap Kepuasan Nasabah dengan Citra Perusahaan Sebagai Variabel Mediasi pada BMT NU Kabupaten Pamekasan - Qonita Qonita (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Currently, very tight competition requires LKMS such as BMT to focus on customers. As an effort to win the hearts of customers BMT needs to implement CRM and ICG strategies, which are strategies for establishing good relationships with customers in supposed to gain satisfaction and a good image of a company. This research aims to determine the direct and indirect influence of CRM and ICG on customer satisfaction through company image as a mediating variable at BMT NU Pamekasan Regency. The research method used is a quantitative method with an explanatory research approach to determine the hypothesis by looking at the relationship or influence. The population in this study were BMT NU customers in Pameksan Regency with a sampling technique using accidental sampling with a sample size of 190 respondents and using primary data obtained through distributing questionnaires. Then the data that has been obtained is analyzed using SmartPLS 3 software. The research results show that CRM directly has a positive and significant effect on customer satisfaction. As well as company image, while ICG has no effect on customer satisfaction but has a result on company image. Besides the research results indirectly show that company image is allow to mediate the relationship between CRM and customer satisfaction but ICG is not allow to mediate at BMT NU Pamekasan Regency.